Pengaruh Komitmen Organisasi dan Pelatihan terhadap Kinerja Karyawan Melalui Loyalitas Sebagai Variabel Moderasi - Rochmadona, Arum; Baidlowi, Imam; Kasnowo, Kasnowo (Jurnal Manajemen Riset Inovasi, 2024)
The increasingly tight level of business competition has resulted in companies being faced with the challenge of improving employee performance in order to maintain the company's survival. Employee performance itself is a fairly complex problem where the level of performance can be influenced by a number of factors such as organizational commitment and job training. Work loyalty is also expected to moderate between Organizational Commitment and Training. Because employees who have a high sense of loyalty can work optimally and have a high sense of responsibility for what they do. This study aims to determine the effect of Organizational Commitment and Training on Employee Performance through Loyalty as a moderating variable at PT Bunga Jaya Jati Bintang Company. This study uses a quantitative approach with data collection techniques using questionnaires. The population of this study was 60 employees with a sample of 60 employees, who were selected as a whole and analyzed using the SPSS (Statistical Package for the Social Sciences) version 26 analysis tool. The results of this study indicate (1) Organizational Commitment has a positive and significant effect on Employee Performance, (2) Training has a positive and significant effect on Employee Performance, (3) Loyalty can moderate (strengthen) the effect of Organizational Commitment on Employee Performance, and (4) Loyalty can moderate (strengthen) the effect of Training on Employee Performance.